Prinsip dan Pengembangan Media IT dalam Pembelajaran Pendidikan Agama Islam - Nora Santi; Aimanun; Mardianto; Nirwana Anas (Medan Resource Center, 2021)
In the era of information technology, Information and Communication Technology (ICT) has become part of the lifestyle, especially in the academic world. The development of science and technology increasingly encourages renewal efforts in the use of technological results in the learning process. Teachers are required to be able to use the tools that can be provided and in accordance with the developments and demands of the times. In addition to being able to use the available tools, teachers are also required to be able to develop skills in making learning media that will be used if the media is not yet available. For this reason, teachers must have sufficient knowledge and understanding of learning media. In learning communication, learning media is needed to increase the effectiveness of achieving learning objectives. By using the media, the interaction between teachers and students is no longer only done through face-to-face relationships. Teachers can provide services without having to deal directly with students. Similarly, students can obtain information in a broad scope from various sources through cyber space or virtual space using computers or the internet.